Dynamic Load Distribution of a Radially Loaded Rolling Bearing - Ya Luo; Keke Ge; Yibin Huang; Wenbing Tu (Shock and Vibration)
Load distribution is a very important indicator that has a great effect on bearing service performance. Unreasonable load distribution is likely to accelerate the bearing failures. The dynamic effects of the moving parts of the rolling bearing have significant influence on the load distribution. In order to study the load distribution of rolling bearings, the dynamic interaction between raceways and balls is considered in detail and a dynamic model of ball bearings subjected to radial loads is presented. The results of the proposed model are compared with those of the traditional static model and the quasi-static model. The dynamic load coefficient and the dynamic angular extent coefficient are defined to show the characteristics of the dynamic load distribution. The effects of radial clearance, the radial load, and the rotational speed on the dynamic load distribution are studied. Through the above research, this paper concludes that the load distribution is greatly influenced by the dynamic effects of moving parts, especially under the conditions of large clearance, light load, or high speed.